Microlensed radio emission from exoplanets. Issue 2 (12th May 2020) - Shiohira, Yuta; Terada, Yuka; Mukuno, Den; Fujii, Yuka; Takahashi, Keitaro
ABSTRACT: In this paper, we investigate the detectability of radio emission from exoplanets, especially hot Jupiters, which are magnified by gravitational microlensing. Because hot Jupiters have orbital periods much shorter than the characteristic time-scale of microlensing, the magnification curve has a unique wavy feature depending on the orbital parameters. This feature is useful to identify radio emission from exoplanets and, in addition to magnification, makes it easier to detect exoplanets directly. We also estimate the expected event rate red of the detectable level of microlensed planetary radio emissions, assuming the Low Frequency Array and the first phase of the Square Kilometre Array.